Assessment of Preventive Behaviors of Osteoporosis in Postmenopausal Women in Fasa, Fars Province Based on the Health Belief Model - Kashfi M; Khani Jeihooni A; Jamshidi H; Bahmandoost M (Preventive Care in Nursing and Midwifery Journal, 2017)
Background: Osteoporosis is the most common metabolic bone disease in postmenopausal women. It seems necessary to determine the factors affecting the adoption of preventive behaviors of osteoporosis in postmenopausal women using the patterns that identify the factors influencing behavior. Objectives: To investigate preventive behaviors of osteoporosis in postmenopausal women in Fasa, Fars Province based on the Health Belief Model. Methods: A cross-sectional study was conducted on 380 postmenopausal women aged over 50 under the coverage of Fasa health centers. Out of the 6 health centers in Fasa, 2 of them were selected based on cluster sampling method. Then, 190 postmenopausal women were selected from each health centers based on simple random sampling by the household number recorded in the health records. The required data were collected using questionnaire including demographic information, awareness inventory, the Health Belief Model scale, and diet and walking performance questionnaire. The data were statistically analyzed in SPSS 22. Results: The construct of perceived susceptibility for diet and walking performance was predictive. In this study, walking performance had a significant relationship with perceived susceptibility (P=0.001, r=0.76), motivation (P=0.001, r=0.65), perceived benefits (P=0.001, r=0.88), and self-efficacy (P=0.001, r=0.69). In addition, diet performance presented a significant relationship with perceived benefits (P=0.001, r=0.68) and self-efficacy (P=0.001, r=0.28). Conclusion: The study results showed that the higher the perceived susceptibility of individuals, the better the preventive behavior of osteoporosis they adopt. The Health Belief Model can be used as an appropriate framework for the design and implementation of educational programs in order to adopt the preventive behaviors of osteoporosis by postmenopausal women.